2023
DOI: 10.3390/jcm12020511
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fatigue, Depression and Anxiety Symptoms in Long COVID Are Strongly Predicted by Neuroimmune and Neuro-Oxidative Pathways Which Are Caused by the Inflammation during Acute Infection

Abstract: Background: Long-term coronavirus disease 2019 (long COVID) is associated with physio-somatic (chronic fatigue syndrome and somatic symptoms) and affective (depression and anxiety) symptoms. The severity of the long COVID physio-affective phenome is largely predicted by increased peak body temperature (BT) and lowered oxygen saturation (SpO2) during the acute infectious phase. This study aims to delineate whether the association of BT and SpO2 during the acute phase and the long COVID physio-affective phenome … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 109 publications
1
13
0
Order By: Relevance
“…The first major finding of this study is that a common core (latent vector) could be extracted from physiosomatic, depressive, and anxiety symptoms, demonstrating that these symptom domains are highly interrelated expressions of the physio-affective phenome of Long COVID. These findings are consistent with our prior findings that a single component drives both physiosomatic and affective symptoms in individuals with Long COVID (Al-Hadrawi, Al-Rubaye et al 2022, Al-Hakeim, Al-Rubaye et al 2023, Almulla, Al-Hakeim et al 2023). In the present investigation, however, the relationships were calculated in patients who had all suffered from acute COVID-19 infection, while in our prior studies, the connections were calculated in healthy controls and participants with long-term COVID.…”
Section: Discussionsupporting
confidence: 93%
“…The first major finding of this study is that a common core (latent vector) could be extracted from physiosomatic, depressive, and anxiety symptoms, demonstrating that these symptom domains are highly interrelated expressions of the physio-affective phenome of Long COVID. These findings are consistent with our prior findings that a single component drives both physiosomatic and affective symptoms in individuals with Long COVID (Al-Hadrawi, Al-Rubaye et al 2022, Al-Hakeim, Al-Rubaye et al 2023, Almulla, Al-Hakeim et al 2023). In the present investigation, however, the relationships were calculated in patients who had all suffered from acute COVID-19 infection, while in our prior studies, the connections were calculated in healthy controls and participants with long-term COVID.…”
Section: Discussionsupporting
confidence: 93%
“…Exosomes act as sustained carriers of SARS‐CoV‐2 spikes on their surface and RNA in their cargo, which may extend the persistence time of the virus after acute COVID infection. High levels of NLRP3 inflammasome and lowered Ca were found in long‐COVID with chronic fatigue, pain, depression, and anxiety disorder 168 …”
Section: Neurological Disorders In Covid‐19 and The Role Of Exosomes ...mentioning
confidence: 97%
“…High levels of NLRP3 inflammasome and lowered Ca were found in long-COVID with chronic fatigue, pain, depression, and anxiety disorder. 168 Because the inflammasome controls the inflammatoryimmunological response in infectious conditions and stressors, NLRP-3 affects the phosphorylation of tau protein and causes tauopathies. 169 The buildup of tau protein underlies most of long-COVID's symptoms.…”
Section: Neurodegenerative and Demyelinating Disordersmentioning
confidence: 99%
“…In a recent previous article co-authored by some of the present’s study collaborators, it was observed that CFS and affective symptoms due to Long COVID are predicted by elevated peak body temperature (PBT) and decreased oxygen saturation (SpO2) during the acute phase of illness (Al-Hadrawi, Al-Rubaye et al 2022). Both PBT and lower SpO2 are indices of the severity of the immune-inflammatory response during acute infection (Al-Jassas, Al-Hakeim et al 2022). In another article by some of this study’s authors, a validated latent vector could be extracted from the CFS, fibromyalgia, depressive and anxiety symptoms due to acute and Long COVID and this latent construct was named the “physio-affective phenome” of acute COVID-19 (Al-Jassas, Al-Hakeim et al 2022) or Long COVID (Al-Hadrawi, Al-Rubaye et al 2022, Al-Hakeim, Al-Rubaye et al 2022, Al-Hakeim, Al-Rubaye et al 2022, Maes, Al-Rubaye et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Both PBT and lower SpO2 are indices of the severity of the immune-inflammatory response during acute infection (Al-Jassas, Al-Hakeim et al 2022). In another article by some of this study’s authors, a validated latent vector could be extracted from the CFS, fibromyalgia, depressive and anxiety symptoms due to acute and Long COVID and this latent construct was named the “physio-affective phenome” of acute COVID-19 (Al-Jassas, Al-Hakeim et al 2022) or Long COVID (Al-Hadrawi, Al-Rubaye et al 2022, Al-Hakeim, Al-Rubaye et al 2022, Al-Hakeim, Al-Rubaye et al 2022, Maes, Al-Rubaye et al 2022).…”
Section: Introductionmentioning
confidence: 99%